Introduction: Open Source and Proprietary Models of Innovation: Beyond Ideology - Charles R. McManis (Washington University Journal of Law & Policy, 2009)
Part I of this Volume consists of introductory articles on business, law, and engineering perspectives on open source innovation. Part II focuses on open source biotechnology, while Part III focuses on open source and proprietary software development. Part IV examines collaborative innovation, the economics of innovation, and two examples of constructed commons—namely universities and a multilateral system for plant innovation for food and agriculture.
Keywords: Open source software; Business perspective on open source innovation; Legal perspective on open source innovation; Engineering perspective on open source innovation; Open source biotechnology; Proprietary software development; Collaborative innovation